The Cost Comparative Analysis of Steel Frame Bridge Installation Work Methodology Between Using Cranes and Using Launching Gantry in Muara Karang Combined Cycle Power Plant 400-500 Mw Project - Fariz Gading Pangestyo; Anjas Handayani (Journal of World Conference (JWC), 2021)
Electrical energy is one of the most important and vital human needs that cannot be separated from daily needs. The case study was taken from the Muara Karang Combined Cycle Power Plant 400-500 MW Project, which is part of a 35,000 MW governmental program that aims to fulfill electricity needs from Sabang to Merauke. In this project, a method of implementing steel-frame bridge installations will be sought in terms of cost. That way, later you will get an efficient installation implementation method. In this study, the authors used secondary data from literature and primary data that taken directly from field observations. Data processing uses statistical tests with the Stepwise method. The cost for the work method using the crane is IDR 367,212,450, while the cost for the work method using the launching gantry is IDR 321,868,085. In the percentage result of the steel frame bridge installation work method, the greatest effectiveness factor is Tool Reach (X11) of 94.5%. Whereas in the work method using launching gantry with the variable that has the greatest effectiveness is the Capacity of Tools Used 76.8%. Judging from these results the factors that have the highest effectiveness to influence the time performance in the implementation of the steel frame bridge installation work method are the tool factor and the material factor.